2011
DOI: 10.1007/s00784-011-0573-4
|View full text |Cite
|
Sign up to set email alerts
|

Saliva in perimenopausal and early postmenopausal women. A 2-year follow-up study

Abstract: This study aims to investigate salivary flow and biochemical constituents of menopausal-age women with the hypothesis that women using hormone therapy (HT) might present better saliva values than non-users. Two hundred HT users and 200 non-users were selected at random from a cohort study of 3,173 peri- and postmenopausal women and invited to a 2-year clinical follow-up study. Clinical examination with saliva sampling was made at baseline and 2 years later. Salivary total protein, albumin, and immunoglobulin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…However, no differences were observed, in this study, on saliva production between women receiving HRT and those not receiving it, similarly to results found on a longitudinal cohort study that investigated salivary flow and biochemical variables in perimenopausal and early post-menopausal women submitted or not to HRT [25]. One possible explanation for that fact might be the low amount of saliva produced by the salivary glands of the oral and pharyngeal mucosa.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, no differences were observed, in this study, on saliva production between women receiving HRT and those not receiving it, similarly to results found on a longitudinal cohort study that investigated salivary flow and biochemical variables in perimenopausal and early post-menopausal women submitted or not to HRT [25]. One possible explanation for that fact might be the low amount of saliva produced by the salivary glands of the oral and pharyngeal mucosa.…”
Section: Discussionsupporting
confidence: 77%
“…HRT has been reported to cause changes in the oral mucosa, possibly improving epithelial integrity [24,25]. However, no differences were observed, in this study, on saliva production between women receiving HRT and those not receiving it, similarly to results found on a longitudinal cohort study that investigated salivary flow and biochemical variables in perimenopausal and early post-menopausal women submitted or not to HRT [25].…”
Section: Discussionsupporting
confidence: 46%
“…In future studies, the effects of hormonal changes on the oral epithelium, periodontium, oral microbiome, the composition of Oral epithelium. The adverse effect of decreased serum estrogen on the mucosa is well known: the oral epithelium becomes thin and atrophic, accompanied by a deterioration of mucosal integrity and immunity 27 , whereas estrogen supplementation and HRT improves mucosal integrity [28][29][30] . The oral mucosa also responds to progesterone 31 , high levels being detrimental, especially in immuno-compromised patients [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen plays a crucial role in immune regulation of hOMECs. Clinical studies have found that post‐menopausal women who have lower levels of estrogen are more susceptible to oral mucosal inflammatory disease, such as OLP 10,12‐14 . However, there is little information about the role and effects of estrogen on this.…”
Section: Introductionmentioning
confidence: 99%